GAMBARAN POLA PENGOBATAN DAN TINGKAT PENGETAHUAN MENGENAI PENGGUNAAN OBAT SELAMA KEHAMILAN DI PUSKESMAS DENPASAR UTARA II BALI - Aprilia, Rizki Mega; Artini, I Gusti Ayu (E-Jurnal Medika Udayana; Vol 6 No 7 (2017): E-Jurnal Medika Udayana, 2017)
Pregnancy is a special condition that needs more attention regarding the nutrition and health of mother. It can directly affect the baby which can cause many unwanted outcomes. Even if drugs can cause unwanted effects, the need of drugs for several cases such as hypertension, asthma, epilepsy, infection, etc., are needed. Drugs i.e. vitamin and mineral is also needed since pregnant women require it more than normal people. This research aims to study about the pattern of drug used in pregnant women in Bali especially in North Denpasar. This research was a descriptive study with cross sectional survey design. Questionnaire had been given to 96 respondents at private midwife practice in North Denpasar II Public Health Center, Bali coverage area on August – October 2014. There were 93.7% pregnant women who used drugs. Total of 216 drugs prescribed with average of 2.24 prescriptions per women. Majority of it was iron supplement which is 26.1%. The drugs were prescribed mostly on first trimester as much as 47.7%. While the drugs category was 97.7% belong to category A drugs and 2.3% was category B drugs. The knowledge of respondent was majority moderate (59, 4%) and there were only 12,5% with good knowledge. Further education about drugs and pregnancy was encouraged to be given by the doctor, midwife, and even nurse to the pregnant women and the family to increase their awareness about drugs used.   Keyword s : pregnancy, pharmacoepidemiology, drugs, pattern, knowledge